The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/jocs.14914
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID‐19 pandemic on congenital heart surgery practice: An alarming change in demographics

Abstract: Background: The aim of this study is to investigate the effect of COVID-19 outbreak on congenital cardiac surgery practice in a single center. Methods: The first case of COVID-19 in our country was seen on March 11th, 2020. The patients operated between March 11th, 2019-and March 10th, 2020 were taken as the pre-COVID group, and those operated between March 11th and May 11th, 2020 were taken as the COVID group. The data was retrospectively collected, and the two periods were compared. Results: Monthly average … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 11 publications
(12 reference statements)
0
15
0
1
Order By: Relevance
“…Studies have reported up to 61% fall in cardiac surgeries during COVID-19 as compared to similar time during previous year [8]. Korun et al, from Turkey, report congenital cardiac surgery reduction during the pandemic to 2/3 of that during the preceding year [9].…”
Section: Discussionmentioning
confidence: 94%
“…Studies have reported up to 61% fall in cardiac surgeries during COVID-19 as compared to similar time during previous year [8]. Korun et al, from Turkey, report congenital cardiac surgery reduction during the pandemic to 2/3 of that during the preceding year [9].…”
Section: Discussionmentioning
confidence: 94%
“…The novel coronavirus-2019 (COVID-19) pandemic at the end of 2019 has imposed an enormous burden on healthcare systems and due to human mobility restrictions, patient referrals to reference centers became difficult and the number of referrals decreased dramatically. [ 5 ] It has become necessary to build our intensive care modality as soon as possible. In patients requiring speeding up the process, it was decided to establish a separate compartment inside the existing neonatal ICU where patients undergoing congenital heart surgery can be followed.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, pediatric CHD surgeries were equally affected. In two separate studies evaluating the effect of COVID-19 on CHD surgeries, the number of surgeries performed https://doi.org/10.1017/S1047951121002754 during 2020 was almost equal to half the number performed during the pre-COVID-19 years 9,10 . Moreover, owing to the increased quest for healthcare services, the suspension of nonemergent and essential surgeries is perceived as a necessity that should be employed at any point during the course of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…In light of the above, several congenital heart disease centers recommended adopting a patient triage that is based on surgical urgency and necessity. This triage can decrease the risk of COVID-19 transmission and ensure the delivery of emergent medical care to all patients, especially in the current era of limited medical resources 9,12,13 . It can provide an effective and just distribution of the available resources among COVID-19 and non-COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%